2011
DOI: 10.1002/lary.22192
|View full text |Cite
|
Sign up to set email alerts
|

Effective use of physician extenders in an outpatient otolaryngology setting

Abstract: Physician extenders may be a valuable asset to an outpatient otolaryngology practice. The adjunctive care provided by physician extenders appears to be cost effective and has the advantages of increasing patient education, promoting physician productivity, and improving management of chronic conditions. Practice types that may benefit from advanced practice providers include group or solo practices with high demand or who need improved efficiency. We discuss five different practice models for incorporation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
23
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 13 publications
(31 reference statements)
0
23
0
Order By: Relevance
“…16 17 18 Studies from other specialties support the scribe role 1920 21 22 23 Evaluations have shown increased medical productivity,1 12 15 16 20 24 25 but not necessarily faster emergency department throughput, for which the literature is in equipoise 17 10 11 13 15 16…”
Section: Introductionmentioning
confidence: 99%
“…16 17 18 Studies from other specialties support the scribe role 1920 21 22 23 Evaluations have shown increased medical productivity,1 12 15 16 20 24 25 but not necessarily faster emergency department throughput, for which the literature is in equipoise 17 10 11 13 15 16…”
Section: Introductionmentioning
confidence: 99%
“…Scribe services are being employed in increasing numbers of EDs and offices across the USA. Independent measures of their productivity gains in the ED are limited .…”
Section: Introductionmentioning
confidence: 99%
“…In other western health systems, EPs are seeing two to three patients per hour with the assistance of medical scribes – the rate depending on the complexity of their patients . Scribes have been used successfully in different ED settings – private, public and academic centres in the USA, also in other speciality office settings . Furthermore these scribe programmes have demonstrated significant cost‐benefit/metric improvement .…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Scribes have been used successfully in different ED settingsprivate, public and academic centres in the USA, also in other speciality office settings. 3,[5][6][7][8] Furthermore these scribe programmes have demonstrated significant cost-benefit/metric improvement. [3][4][5][6][7] The American College of Emergency Physicians suggests improvements in productivity of about 20% can be expected.…”
Section: Introductionmentioning
confidence: 99%